Effects of 'green' training on pro-environmental behaviors and job satisfaction: Evidence from the Italian healthcare sector. (20th July 2019) - Pinzone, Marta; Guerci, Marco; Lettieri, Emanuele; Huisingh, Donald
Abstract: Literature of cleaner production shows that, for improving the environmental performance of the organization, it is important to provide employees with specific green-related competencies and to buy their commitment towards the green cause. Accordingly, studies explored the effects on environmental performance of green human resource management, in which green training (i.e. interventions aimed at developing green-related competencies) resulted as a key practice. This paper enriches the fast growing literature on green training in two directions. First, showing that green training is associated with employees engagement in voluntary pro-environmental behaviours; our evidence shows this relationship is mediated by the fact that green training enacts a sense of challenge in employees, which motivates them to engage in green-oriented discretionary effort. Second, the paper shows that – diversely from other types of training - green training makes employees more satisfied with their jobs; this relationship emerged as mediated by the employees' perception that green training is as a form of support provided by their employer, which makes their professional experience more satisfying. Those results are achieved through a survey to 260 healthcare professionals. This sector was selected as an extreme case, as current research has demonstrated that it is hard for healthcare professionals – given their organizational autonomy, and professional values - to engage in green-related behaviours, and to see their employer's support on the green cause as a driver for their job satisfaction. Implication for theory and practice are presented and discussed. Graphical abstract: Image 1 Highlights: Green training positively affects employees' pro-environmental behaviours and job satisfaction. Green goal difficulty partially mediates the effects of green training on pro-environmental behaviours. Green perceived organizational support partially mediates the effects of green training on job satisfaction. Green training is an effective practice to gain professionals' buy-in in environmental activities. Managers are recommended to use green training to improve their organizations' sustainability.